2017
DOI: 10.18632/oncotarget.21935
|View full text |Cite
|
Sign up to set email alerts
|

Development of diagnostic model of lung cancer based on multiple tumor markers and data mining

Abstract: ObjectiveTo develop early intelligent discriminative model of lung cancer and evaluate the efficiency of diagnosis value.MethodsBased on the genetic polymorphism profile of CYP1A1-rs1048943, GSTM1, mEH-rs1051740, XRCC1-rs1799782 and XRCC1-rs25489 and the methylations of p16 and RASSF1A gene, and the length of telomere in the peripheral blood from 200 lung cancer patients and 200 health persons, the discriminative model was established through decision tree and ANN technique.ResultsACU of the discriminative mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…In the present study, increase in the number of markers (peptides) in high-dimensional classifier resulted in improved performance, which is in good agreement with previous studies showing a clear advantage of using multiple features as compared to single markers for predictive disease modeling 2830 . This observation seems consistent, provided that the variables are truly associated with the investigated outcome to positively influence the model training phase.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, increase in the number of markers (peptides) in high-dimensional classifier resulted in improved performance, which is in good agreement with previous studies showing a clear advantage of using multiple features as compared to single markers for predictive disease modeling 2830 . This observation seems consistent, provided that the variables are truly associated with the investigated outcome to positively influence the model training phase.…”
Section: Discussionsupporting
confidence: 92%
“…Estimates show that COPD becomes the third leading cause of death in 2017, worldwide. Recent studies have indicated that the occurrence of lung cancer is a multiple-factors and multiple-step process, and it is the result of interaction between genetic and environmental exposure factors (13). COPD is a complex disease that is influenced by genetic factors, environmental influences, and genotype-environment interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications [ 13 , 14 ] have shown that models based on data mining improve the diagnostic effect and profound significance for diagnostic of early stage lung cancer. A Chinese group [ 14 ] showed that the AUC level of each discriminative model was improved by about 10% based on multiple tumor markers and data mining compared with the diagnostic model based on different tumour markers, which indicates that the sensitivity and specificity of diagnosis can be substantially improved through combining different tumor markers compared to an individual tumor marker. However, the information about data mining based decision support systems for survival in lung cancer is sparse.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown the capacity of data mining-based models to predict the onset of lung cancer [ 13 , 14 ]. However, the study of the survival outcome with this approach is sparse.…”
Section: Introductionmentioning
confidence: 99%